Search for diboson resonances in hadronic final states in 139 fb−1 of pp collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2019)
Narrow resonances decaying into W W, W Z or ZZ boson pairs are searched for in 139 fb−1 of proton-proton collision data at a centre-of-mass energy of s√ = 13 TeV recorded with the ATLAS detector at the Large Hadron Collider from 2015 to 2018. The diboson system is reconstructed using pairs of high transverse momentum, large-radius jets. These jets are built from a combination of calorimeter- and tracker-inputs compatible with the hadronic decay of a boosted W or Z boson, using jet mass and substructure properties. The search is performed for diboson resonances with masses greater than 1.3 TeV. No significant deviations from the background expectations are observed. Exclusion limits at the 95% confidence level are set on the production cross-section times branching ratio into dibosons for resonances in a range of theories beyond the Standard Model, with the highest excluded mass of a new gauge boson at 3.8 TeV in the context of mass-degenerate resonances that couple predominantly to gauge bosons.